2007
DOI: 10.1002/chem.200601225
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Dynamic Characterization of Copper(II) Binding of the Human Prion Protein Outside the Octarepeat Region

Abstract: Human prion protein (hPrP) fragments encompassing the 91-120 region, namely hPrP92-100 (SP1), hPrP106-113 (SP2), hPrP91-120 (LP1), and hPrP91-114 (LP2), were considered for delineation of the Cu(II)-binding site(s). NMR and EPR spectroscopy results obtained from LP1 or LP2 were compared with those obtained from SP1 and SP2. The coexistence of two binding sites, one centered at His96 and the other at His111, was evidenced and ratified by ESI mass spectrometry at low and high metal:peptide ratios. While room-tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
71
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(79 citation statements)
references
References 66 publications
(70 reference statements)
8
71
0
Order By: Relevance
“…[77][78][79][80][81][82][83][84][85][86][87] Moreover, the hPrP91-127 region, which is next to the repeat domain, provides two further copper(II) binding sites, each associated with a histidine residue, His96 and His111, respectively. [67,70,72,73,75,76,[88][89][90][91][92][93][94][95][96] Although there is no general consensus, most of the results obtained so far indicate His111 as the preferential, if not exclusive, copper(II) binding site. [67,72,73,75,76,90,91,95,96] Our systematic studies carried out on small peptide fragments of PrP led to the same conclusions, and the high copper(II) binding affinities of the His96, [97] His111, [98] and even His187 [99] residues have unambiguously been demonstrated.…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…[77][78][79][80][81][82][83][84][85][86][87] Moreover, the hPrP91-127 region, which is next to the repeat domain, provides two further copper(II) binding sites, each associated with a histidine residue, His96 and His111, respectively. [67,70,72,73,75,76,[88][89][90][91][92][93][94][95][96] Although there is no general consensus, most of the results obtained so far indicate His111 as the preferential, if not exclusive, copper(II) binding site. [67,72,73,75,76,90,91,95,96] Our systematic studies carried out on small peptide fragments of PrP led to the same conclusions, and the high copper(II) binding affinities of the His96, [97] His111, [98] and even His187 [99] residues have unambiguously been demonstrated.…”
Section: Introductionmentioning
confidence: 71%
“…[67,70,72,73,75,76,[88][89][90][91][92][93][94][95][96] Although there is no general consensus, most of the results obtained so far indicate His111 as the preferential, if not exclusive, copper(II) binding site. [67,72,73,75,76,90,91,95,96] Our systematic studies carried out on small peptide fragments of PrP led to the same conclusions, and the high copper(II) binding affinities of the His96, [97] His111, [98] and even His187 [99] residues have unambiguously been demonstrated. A comparison of the thermodynamic stabilities of the histidinecontaining fragments revealed that the peptides that encompass the amino acid sequences outside the octarepeat domain are even more efficient chelators of copper(II) than the single octarepeat fragments.…”
Section: Introductionmentioning
confidence: 71%
“…Furthermore, a fifth Cu(II) ion binding site was recently identified as a region involved in histidine 95 and histidine 110 in the neighborhood of the OR region. Some studies have suggested that Cu(II) binding to this fifth site is correlated with the conversion into a protease-resistant species and the increase of -sheet conformation in PrP [13][14][15].…”
Section: Resultsmentioning
confidence: 99%
“…The line broadening was not detected in moPrP(D143R1), indicating a long interspin distance (>20 Å). There was a possibility that Cu(II) ion bonded to the sites other than His186, i.e., the octarepeat region from codon 60 to 90 [11][12][13] and the region between amino acids 95 and 110 [14,15], were associated with the nitroxide spin probe of these recombinant prion proteins via an unexpected tertiary structure of PrP or intermolecular interaction. Therefore we tested the effect of Cu(II) on moPrP(Y156R1,H186A), which is a double mutation for disruption of the histidine residue for the Cu(II) binding site.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation